Corporate social responsibility, institutional investors’ ownership, financial restatements and sell-side analysts’ stock recommendations - Qasem, Ameen Ali Mohammed (2018)
In Malaysia, the capital market regulators have recently given prominent attention to issues such as corporate responsibility (CSR), shareholder activism and integrity in financial reporting by issuing the Sustainability Reporting Guide (2015) and Malaysian Code for Institutional Investors (2014). Given the importance of these issues, this study examines whether CSR, institutional investors’ ownership, and financial restatements influence stock recommendations made by analysts. It employs a dataset from a panel of 285 Malaysian public listed companies (PLCs) for the period 2008 to 2013 (737 company-year observations). The results show a positive and significant influence of CSR reporting on the stock recommendations, which means that analysts issue more favourable stock recommendations for companies with higher CSR disclosures. Further, the findings indicate that the presence of both transient and dedicated institutional investors are viewed positively by analysts. In particular, the results indicate that analysts issue more favourable stock recommendations for the companies with higher levels of transient and dedicated institutional investors’ ownership. In addition, the results also show that analysts tend to give favourable stock recommendations for companies that restated their financial statements, contrary to expectation. These findings imply that analysts tend to echo government initiatives by giving favourable stock recommendations to companies with greater engagement in CSR activities and the ability to attract institutional investors. The findings also suggest that analysts view financial restatements as informative rather than opportunistic. Overall, these findings should be useful to PLCs and policymakers. PLCs might use the findings to understand the preferences of sell-side analysts towards CSR engagement. Furthermore, policymakers might use it to recognize the important role played by institutional investors in monitoring investee companies and to understand how analysts perceive and evaluate restated companies.